Influencia de los valores humanos en la disrupción de los estudiantes de quinto grado de educación básica de la Escuela 28 de Mayo, Cantón Babahoyo, Provincia de Los Ríos - León Aleman, Miguel Bryan (2020)
Framed the values that in this thesis are expected to spread taking into account the objectives set to solve problems of aggression carried out by students in the classrooms and outside them currently is a social, educational, human causative male problem in teachers who have to fight Day by day with these problems, our acts are most frequently provoked which cause disruption in the classroom, damaging the normal teaching-learning process, generating males among the fathers and mothers of families, the problem of the influence on the interruption of students from Fifth Grade of the School May 28 should be aware of the problems that have a short or long term concern us not only in our institution but in most schools in the country or the world. The education in values will not be a panacea to change the behavior of our students but if you work with enthusiasm and in a shared way, without being too ambitious, it will serve to take positions and commitments that imply changes in behavior in specific situations. It is a fact that when applying methodological guides and introducing the transversal axes that integrate the fields of being, saber, doing, and living together, it gives students a comprehensive and meaningful vision of their learning since it proposes an interdisciplinary treatment with problems and daily needs of children. In short, educating in the moral dimension of the person means educating their autonomy, their rationality, their capacity for dialogue, in order to build principles and norms that act on their knowledge and on their behavior that implies when thinking and acting of each being human, so that you respect the freedom of all people, its ethical maturation is possible